2001
DOI: 10.1590/s0103-50532001000600015
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Alignment Dependence of Ethylene Glycol Flow on the Chemical Nature of the Solid Surface (Borosilicate and SnO2)

Abstract: Este trabalho estuda o fluxo de etileno glicol (MEG) sobre duas superfícies sólidas com constituições químicas diferentes: borossilicato e dióxido de estanho (SnO 2 ). O alinhamento intermolecular, determinado como polarização e anisotropia, mostrou dependência da natureza química do sólido. A razão entre as tensões interfaciais dinâmicas foi 1.09 ± 0.07, devendo ser maior para MEG/borossilicato do que para MEG/SnO 2 . A razão da capilaridade foi 0.92 ± 0.06, sendo menor para MEG/borossilicato. Medidas estátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Fluorescence detection can be done by two laser spectroscopic techniques: Laser induced¯uorescence (LIF) and uorescence depolarization or polarized laser-induced uorescence (PLF) [4,6]. In LIF the¯uorescence emission is collected by a detection system regardless to its polarization and the data give direct information on how the probes align upon excitation.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescence detection can be done by two laser spectroscopic techniques: Laser induced¯uorescence (LIF) and uorescence depolarization or polarized laser-induced uorescence (PLF) [4,6]. In LIF the¯uorescence emission is collected by a detection system regardless to its polarization and the data give direct information on how the probes align upon excitation.…”
Section: Theorymentioning
confidence: 99%
“…The initially low MEG polarization and anisotropy may be due to strong interfacial interactions with borosilicate [4]. The liquid has hydrogen atoms and hydroxyls, whilst the solid surface is composed by highly electronegative atoms and has been cationized.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fluorescence depolarization was applied for the first time to evaluate dynamic Γ SL of liquids flowing as thin sheets on two flat surfaces with different chemical constitutions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have shown that for thin channels the flow consists mainly of superposed boundary layers where interfacial chemical interactions become predominant over bulk flow [13]. Recently, PLF-FI was used to evaluate relative dynamic Γ SL for monoethylene glycol flowing on either glass or tin dioxide and it was found that dynamic Γ SL was stronger for glass than for tin dioxide [5].…”
Section: Introductionmentioning
confidence: 99%